2021
DOI: 10.3174/ajnr.a7174
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the Woven EndoBridge Device for Treatment of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-analysis

Abstract: BACKGROUND:The Woven EndoBridge device has been increasingly used to treat wide-neck aneurysms, particularly ruptured ones. PURPOSE: Our aim was to investigate the safety and efficacy of the Woven EndoBridge device in the treatment of ruptured intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…The Woven EndoBridge (WEB) device (Microvention, CA) currently represents the most extensively studied intrasaccular device,1 2 and has proven to be a very safe option to treat wide-necked bifurcation aneurysms 3. Since its introduction, angiographic results have improved year on year, likely due to the sharing of operator experiences in device sizing,4 5 and yet 5–12% of patients still require retreatment 3 6–10…”
Section: Introductionmentioning
confidence: 99%
“…The Woven EndoBridge (WEB) device (Microvention, CA) currently represents the most extensively studied intrasaccular device,1 2 and has proven to be a very safe option to treat wide-necked bifurcation aneurysms 3. Since its introduction, angiographic results have improved year on year, likely due to the sharing of operator experiences in device sizing,4 5 and yet 5–12% of patients still require retreatment 3 6–10…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the reported literature, as Youssef et al [ 14 ], in a study involving 48 patients with ruptured IAs, reported adequate occlusion in 92.3% at a median follow up of 5.5 months, and Cortez et al [ 15 ], in a study of 91 patients with ruptured IAs, demonstrated 80% adequate occlusion at a mean follow up of 3.4 months. A subsequent meta-analysis by Essibayi et al [ 16 ] pooled 487 patients with 496 ruptured aneurysms treated with WEB, reporting an adequate occlusion rate of 87.3%. The single mortality in our series was unrelated to WEB deployment.…”
Section: Discussionmentioning
confidence: 99%
“…WEB meta-analyses have pointed to a high rate of selection bias in the WEB studies analyzed [ 20 , 21 , 22 ]. In the study period, our Center treated all WNBA patients with WEB, adding quality to this long-term follow-up study [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…WEB meta-analyses have pointed to a high rate of selection bias in the WEB studies analyzed [ 20 , 21 , 22 ]. In the study period, our Center treated all WNBA patients with WEB, adding quality to this long-term follow-up study [ 21 , 22 ]. Moreover, this study is the only one assessing a long-term follow-up exclusively by DSA, the gold standard technique for cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%